PENGARUH PENDAPATAN ASLI DAERAH DAN ASET TETAP TERHADAP BELANJA PEMELIHARAAN: SEBUAH BUKTI EMPIRIS DARI PEMERINTAH DAERAH DI INDONESIA DI MASA PANDEMI COVID-19 - Rusyda Zahra; Syukriy Abdullah; Adnan Adnan; Fifi Yusmita (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
The purpose of this study is to provide empirical evidence of the effect of Local Own Revenue (PAD) and Fixed Assets (AT) on Maintenance Expenditure (BP) at local governments in Indonesia during the Covid-19 pandemic using a multiple linear regression model. The data used is secondary data sourced from the audited local government financial statements (fiscal year 2020) of 215 local governments as the sample. We used the purposive sampling method. The sample criteria are local governments experiencing a deficit in 2019 and obtaining an unqualified opinion (WTP) in 2020. The results showed that PAD had a significant effect, while the AT variable did not have a significant effect on BP. These results prove that during the Covid-19 pandemic, the allocation of maintenance expenditures by local governments was not based on the amount of existing fixed assets.